New Evidence on the Role of Catalase in Escherichia Coli-Mediated Biocorrosion - Paez-Collio, M; Paez-Collio, M; Zagal-Moya, J; Zagal-Moya, J; Vasquez-Guzman, C; Monsalve-Gonzalez, A; Melo-Hurtado, F; Pavez-Irrazabal, J; Pavez-Irrazabal, J; Gulppi-Cabra, M; Gulppi-Cabra, M; Azocar-Guzman, M; et al. (2013)
Sin Editorial Disponible